Bioflocculation in natural and engineered systems: current perspectives. (17th November 2018) - Srivastava, Ankita; Seo, Seong-Hyun; Ko, So-Ra; Ahn, Chi-Yong; Oh, Hee-Mock
Abstract: Microorganisms have the tendency to accumulate at interfaces through the release of extracellular polymeric substances to form aggregates such as films or flocs. This physical association leads to different modes of interactions among cells and the subsequent development of functionally and metabolically diverse consortia. Aggregation of cells in aqueous suspensions often results in the formation of flocs, which are hotspots of enhanced microbial processes. This has important implications for the dynamics of organic and inorganic matter in varied ecosystems. These microbial flocs are not only important components in nutrient turnover, decomposition, and sinking flux but also facilitate contaminant removal and treatment of wastewater and biomass harvesting. Greater insight into the multitude of interactions between microorganisms in flocs would be useful to enhance the efficiency of bioflocculation processes. This review covers the fundamental aspects and outlines the role of bioflocculation in controlled industrial processes and in nature.